PERANAN ROSNANIAR DALAM MEMAJUKAN PENDIDIKAN DI RIAU TAHUN 1962-2008 - Yulia Yantika; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Rosnaniar is one of the leaders in advancing education in Riau. Rosnaniar has a role in advancing education in Riau. The purpose of this study is to find out the curriculum vitae of Rosnaniar, to find out the role of Rosnaniar in advancing education, to find out what achievements Rosnaniar achieved in advancing education. The result of this study were that Rosnaniar promoted education starting from being a teacher and lecturer, Rosnaniar while entering politics and becoming a member of the Indonesian parliament stting on an education commission and participating in proposing the development and active of lectures at IAIN Riau, Rosnaniar in advancing education succeeded in establishing a foundation for da’wah thatn oversaw the educational institution Al Izhar Scholl, Rosnaniar who also championed the regional Indonesian child protection commission formed and became chairman, Rosnaniar was at the time the collaboration agency of the women organization was appointed as the head of the education section and at that time also established`a kindergarten and Rosnaniar as the principal of his school. The method used in this study is qualitative and the data obtained from interviews are added to the data obtained from the books and archives obtained from the result of interviews and literature then analyzed in their own language. As for the place of research in writing this scientific paper is Pekanbaru. Data collection techniques used are documentation, interviews, observations, and related literature in the role of the figure Rosnaniar in advancing education in Riau.Key Words: Rosnaniar, Advancing Education in Riau, Role